Problemmatika sosial terhadap pembelajaran di era new normal (Studi kasus melek huruf) pada SMA Negeri 1 Biak Barat - Yani Talakua; Muhammad Aqil (Sekolah Tinggi Pariwisata Mataram, 2021)
Abstract Learning is a learning process built by teachers to develop creative thinking that can improve students' thinking skills, as well as an effort to acquire intelligence and behavior. With that in the learning of teachers and students must be intertwined so that student learning outcomes can be achieved optimally. Shows activities carried out by someone who is conscious or intentional which refers to a person's activity in carrying out mental aspects that allow changes to occur in him. But in reality there are obstacles that are felt in learning in every school, one of which is literacy which we cannot avoid from all categories of children in schools. Literacy is the ability to identify, understand, translate, create, communicate and process the contents of a series of texts contained in printed and written materials related to various situations. The ability to read and write is considered important because it involves continuous learning by a person so that that person can achieve his goals, where this is directly related to how a person gains knowledge, explores his potential, and participates fully in the wider community.In the learning process at SMA Negeri 1 Biak Barat, it is carried out at home with the teacher giving assignments for students to study at home, one of which is in the form of a module. Even though there are social media applications such as Whatshap (WA), Zoom, Google Clash Room, Telegram which are applied for online learning, only 10% can use them, while only 90% of students cannot use these applications. Even though 10% of students can apply the application, it is less effective because 90% of students cannot apply the application. That way the teacher gives assignments and materials as well as a time limit to work on so that all students can study regularly by implementing a learning system in the form of modules.